Examining the Dynamic Relationship between Oil Prices and Stock Market: New Evidence from Kuwait - Alawadhi, Salah A.; Longe, Adedayo E. (International Journal of Economics and Financial Issues, 2026)
Despite oil revenues making up 90% of government revenue, Kuwait’s stock market is surprisingly disconnected from oil price movements. This study analyzes the relationship between oil price shocks and stock market performance in Kuwait, a major oil-exporting nation sensitive to global oil price fluctuations. Using autoregressive distributed lag (ARDL) model and daily data from September 2015 to May 2025, the study investigates both the short and long-run dynamics of this relationship, with particular focus on optimal lag effects. The ARDL bounds test reveals no evidence of a long- term cointegration between Dubai oil prices and the Kuwait stock market index, suggesting that oil price changes do not exert a persistent effect on Kuwait’s equity market. However, short-run results indicate a significantly positive immediate response of stock returns to oil price increases, followed by weaker and mixed lagged effects. The findings indicate that investor sentiment and speculative activity may drive short-term stock market reactions in Kuwait, while structural features like the presence of a sovereign wealth fund and heavy government involvement limits long-term volatility. This study contributes to the understanding of oil-financial market linkages in resource-dependent economies and provides empirical evidence to guide policy and investment strategy in Kuwait.